'Blind' warfare: radio propaganda dynamics in South Africa during the Second World War. Issue 4 (2nd October 2022) - Monama, Fankie L.
Abstract : During the Second World War, the three-year old South African Broadcasting Corporation (SABC) spearheaded the Union of South Africa's radio propaganda effort to induce national support. Based strongly on archival sources, this article aims to illustrate critically, the dynamics of radio propaganda in support and maintenance of the Union government's war effort in a contested space and politically charged environment. It reflects on the war of words waged primarily by Nazi Germany's Zeesen Radio, targeting the ultra-nationalist Afrikaner opposition to instigate them against the government, and the SABC's counterpropaganda effort. It delineates the SABC's radio propaganda on multiple battlefronts: starting on the back-foot to contest Zeesen, mobilising the homefront, facilitating recruitment as well as boosting civilian and military morale. Moreover, the article reflects on the role of 'pirate' radio stations in contesting the propaganda space; and also alludes to the constraints of the radio propaganda effort during the war.